Segmentation Management Analysis Of Zakat, Infaq, And Sadaqah (ZIS) Distribution In East Lombok Regency - Arwin Yafi Rahmatullah (International Journal of Sociology of Religion, 2023)
BAZNAS East Lombok Regency is a non-structural government forum at the Regency level which is tasked with managing zakat, infaq and shadaqah funds in East Lombok Regency. Segmentation is an effort to maximize the distribution of ZIS that has been collected to be distributed to those entitled to receive it. Segmentation of zakat distribution based on the Qur'an surah at-taubah verse 60 namely fakir, poor, slaves, gharimin, muallaf, fisabilillah, travelers who lack provisions, amil zakat. The purpose of this study was to determine how the distribution of zakat in the baznah of East Lombok district. The method used in this research is qualitative research by reviewing the literature and analyzing the data. Data collection techniques using observation and interviews. The results showed that the distribution of zakat by the baznas of East Lombok district was optimal and right on target in its distribution, based on the segmentation that had been determined.